2017
DOI: 10.18632/oncotarget.22284
|View full text |Cite
|
Sign up to set email alerts
|

Combined venetoclax and alvocidib in acute myeloid leukemia

Abstract: More effective treatment options for elderly acute myeloid leukemia (AML) patients are needed as only 25–50% of patients respond to standard-of-care therapies, response duration is typically short, and disease progression is inevitable even with some novel therapies and ongoing clinical trials. Anti-apoptotic BCL-2 family inhibitors, such as venetoclax, are promising therapies for AML. Nonetheless, resistance is emerging. We demonstrate that venetoclax combined with cyclin-dependent kinase (CDK) inhibitor alvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 60 publications
5
52
1
Order By: Relevance
“…Down-regulation of transcription by CDK9 inhibition broadly and preferentially affects proteins with a short half-life, such as MCL-1 (161)(162)(163). Consistent with this evidence, alvocidib treatment has been shown to decrease MCL-1 levels in AML and chronic lymphocytic leukemia cells (Figure 2C) (30,162,164). Alvocidib induces apoptosis in many tumor cell lines, including those derived from lymphoma, MM, and AML (8).…”
Section: Cdk7 and Cdk9supporting
confidence: 55%
See 3 more Smart Citations
“…Down-regulation of transcription by CDK9 inhibition broadly and preferentially affects proteins with a short half-life, such as MCL-1 (161)(162)(163). Consistent with this evidence, alvocidib treatment has been shown to decrease MCL-1 levels in AML and chronic lymphocytic leukemia cells (Figure 2C) (30,162,164). Alvocidib induces apoptosis in many tumor cell lines, including those derived from lymphoma, MM, and AML (8).…”
Section: Cdk7 and Cdk9supporting
confidence: 55%
“…An alternative approach is to indirectly inhibit the antiapoptotic function of MCL-1. Indirect targeting of MCL-1 by inhibition of specific CDK isoforms that regulate transcription, particularly CDK9 or CDK7, has shown promising preclinical and clinical outcomes (8,29,30).…”
Section: Bcl-2 Family Of Proteins Including Mcl-1 In Aml Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Bogenberger et al showed that alvocidib (also known as flavopiridol), a potent CDK9 inhibitor, downregulated MCL-1 expression and increased BIM expression, inducing synergistic apoptosis when combined with venetoclax in venetoclax-resistant AML cell lines (such as OCI-AML3), patient-derived samples, and a mouse xenograft model of OCI-AML3. 40 Knorr et al demonstrated that MLN4924 (also known as pevonedistat), an inhibitor of the Nedd8 activating enzyme, inactivated E3 cullin ring ligases, causing accumulation of the cullin ring ligase substrate c-Myc, which transactivated the PMAIP1 gene encoding NOXA, inducing upregulation of NOXA and subsequent MCL-1 inhibition. This led to synergistic apoptosis when combined with venetoclax both in cell lines and primary patient samples.…”
Section: Combination Strategies To Boost Venetoclax Activity and Overmentioning
confidence: 99%